The Integrated PBL-DMM: A Learning Model to Enhance Student Creativity - Hidayati, Nurkhairo; Zubaidah, Siti; Suarsini, Endang; Praherdhiono, Henry (Pedagogika, 2019)
The present study aimed to test the effectiveness of two learning models, namely Problem-Based Learning (PBL) and Integrated Problem-Based Learning and Digital Mind Maps (PBL-DMM) in improving student creativity. This experiment employed a pretest-posttest control group design and involved 103 participants. An essay test was used to evaluate the participants’ creativity. The results showed that both PBL and PBL-DMM had an effect on creativity, yet among these two learning models, PBL-DMM was considered more effective to boost student creativity.